Efforts to Increase Hemoglobin Levels Through the Administration of Snakehead Fish Nuggets in Postpartum Mothers in Sereh Village, Sentani District, Jayapura Regency - Mogan, Martina; Trisnawati, Endang; Kadiwaru, Since; Rengil, Yanti (Indonesia Berdaya, 2024)
This Community Service aims to improve the knowledge of postpartum mothers about protein-rich nutrition and factors that can inhibit iron absorption. The methods used include counseling, teaching the preparation of snakehead fish nuggets, and health examinations. This activity was conducted in Sereh Village, Sentani, from May to November 2023, with stages including leaflet distribution, nutritional counseling, and hemoglobin level checks before and after consuming nuggets for 14 days. Prior to the main activities, a trial for nugget preparation was conducted, followed by home visits for observation and evaluation. The hemoglobin level checks revealed that 10 (38.46%) postpartum and breastfeeding mothers experienced mild anemia, while 16 (61.54%) did not have anemia, with an average hemoglobin level of 10.196 g/dl. After consuming 100 grams of nuggets daily for 14 days, changes in hemoglobin levels were observed, with mothers who previously experienced mild anemia transitioning to a non-anemic status. The average hemoglobin level after consuming snakehead fish nuggets was 12.308 g/dl, with an average increase of 2.116 g/dl before and after nugget consumption. The conclusion of this community service activity indicates that postpartum mothers experienced an increase in knowledge regarding the importance of protein-rich nutrition and factors that can inhibit iron absorption.